2017
DOI: 10.1186/s40494-017-0154-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of multispectral and hyperspectral imaging systems for digitisation of a Russian icon

Abstract: In a study of multispectral and hyperspectral reflectance imaging, a Round Robin Test assessed the performance of different systems for the spectral digitisation of artworks. A Russian icon, mass-produced in Moscow in 1899, was digitised by ten institutions around Europe. The image quality was assessed by observers, and the reflectance spectra at selected points were reconstructed to characterise the icon's colourants and to obtain a quantitative estimate of accuracy. The differing spatial resolutions of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 24 publications
(18 reference statements)
1
24
0
Order By: Relevance
“…Hyperspectral systems produce geometric distortions due to the scan motion, to the arrangement of dispersion optics, from the lens itself and also from alignment errors with respect to the work of art. The RRT results showed that not only were the spectral results highly variable, but the resulting image geometries were often equally so (MacDonald et al 2017).…”
Section: Geometric Calibrationmentioning
confidence: 99%
“…Hyperspectral systems produce geometric distortions due to the scan motion, to the arrangement of dispersion optics, from the lens itself and also from alignment errors with respect to the work of art. The RRT results showed that not only were the spectral results highly variable, but the resulting image geometries were often equally so (MacDonald et al 2017).…”
Section: Geometric Calibrationmentioning
confidence: 99%
“…The distinction between multispectral and hyperspectral imaging is not clearly defined but it is agreed that hyperspectral imaging provides higher spectral resolution collecting several thousand (200 or more) contiguous, narrow bands, thus allowing for the reconstruction of almost continuous reflectance spectrum [116] (Figure 19). In contrast, an imaging sensor is considered as multispectral if it registers a small number (usually not more than 20) of discrete spectral bands of bandwidths ranging from 20 to 50 nm [117], which may not be equal in bandwidth and are not necessarily adjacent to each other [115]. Figure 19.…”
Section: Multispectral and Hyperspectral Imagingmentioning
confidence: 99%
“…On the other hand, this knowledge allows the art historians for verification of the object's authenticity. Pigment identification commonly involves the use of VIS-NIR range of spectrum [117,120,124,126,147,148] as the signatures of most inorganic pigments vary significantly in this range, so the spectral information is sufficient to differentiate them. However, to tell apart organic materials like binders, varnishes, or organic pigments, the spectrum of longer wavelengths like SWIR and MWIR is usually needed [149].…”
Section: Multispectral and Hyperspectral Imagingmentioning
confidence: 99%
“…Although various general guidelines exist for performing these steps [32], the lack of a standard protocol is recognized by the community. Capturing the spectral images of icons with several cameras was studied by the authors of [33][34][35] in an imaging campaign with a round robin format among ten European institutes. MacDonald et al [33] compared multi-and hyperspectral measurements from manually-selected points.…”
Section: Introductionmentioning
confidence: 99%
“…Capturing the spectral images of icons with several cameras was studied by the authors of [33][34][35] in an imaging campaign with a round robin format among ten European institutes. MacDonald et al [33] compared multi-and hyperspectral measurements from manually-selected points. They reported high variations in the image quality and poor spectral estimation performance due to specular reflections from the glossy and metallic areas.…”
Section: Introductionmentioning
confidence: 99%